Examining choice to advance gender equality in breeding research - Polar, Vivian; Mohan, Rohini Ram; McDougall, Cynthia; Teeken, Béla; Mulema, Annet A.; Marimo, Pricilla; Yila, Jummai Othniel (International Food Policy Research Institute, 2021)
Breeding is a technical pillar of CGIAR research: the animal/fish breeds, and plant varieties developed are international public goods that contribute to agricultural development for low-income contexts worldwide. Gender equality and women’s empowerment are critical social dimensions underpinning agricultural development in these contexts. Progressing toward gender equality in agriculture requires that women, as well as men, have equal capabilities to make decisions about agricultural innovation, and specifically technology choice. Current evidence, however, suggests the situation here is not yet equal. Nevertheless, despite ongoing inequalities, there is a dearth of literature on the connection between gender and breeding in agricultural research. This chapter critically examines what has been done to address gender dynamics in (current) breeding structures and processes, and what more can be done so that breeding programs contribute to advancing gender equality. We are specifically concerned with technology choices in relation to the plant variety or animal/fish breed by resource-poor smallholders in low-income countries. The chapter explores how CGIAR and public breeding programs generate options based on user needs, preferences, and constraints, and the institutional requirements needed to develop them in such a way that they contribute to gender equality and women’s empowerment.